Association of Suboptimal Antiretroviral Therapy Adherence With Inflammation in Virologically Suppressed Individuals Enrolled in the SMART Study. (22nd December 2017) - Castillo-Mancilla, Jose R; Phillips, Andrew N; Neaton, James D; Neuhaus, Jacqueline; Collins, Simon; Mannheimer, Sharon; Pett, Sarah; Touzeau-Römer, Veronique; Polizzotto, Mark N; Lundgren, Jens D; Gardner, Edward M; ,
Abstract: Suboptimal (ie, <100%) antiretroviral therapy (ART) adherence has been associated with heightened inflammation in cohort studies, even among people with virologic suppression. We aimed to evaluate this association among participants in the Strategies for Management of Antiretroviral Therapy (SMART) study who had virologic suppression (HIV-1 VL < 200 copies/mL) at enrollment. Based on self-reported adherence (7-day recall), plasma concentrations of interleukin 6 and D-dimer were 9% (95% confidence interval [CI], 1%–18%; P = .02) and 11% (95% CI, 1%–22%; P = .03) higher in participants who reported suboptimal vs 100% adherence, respectively. These findings confirm previous observations and support the hypothesis that suboptimal ART adherence, even in the context of virologic suppression, may have significant biological consequences. ClinicalTrials.gov number NCT00027352